PERTANGGUNGJAWABAN HUKUM LEMBAGA KEUANGAN TERHADAP TINDAKAN MELAWAN HUKUM DEBT COLLECTOR - evans Winata (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2026)
Debt collection practices by debt collectors in Indonesia are frequently characterized by unlawful actions such as violence, intimidation, and misuse of personal data. The legal issue that arises concerns the ambiguity regarding financial institutions' liability for debt collectors' actions, whether they are internal employees or external partners. This normative research analyzes the legal construction of the tripartite relationship among financial institutions, debt collectors, and debtors, as well as the application of the vicarious liability doctrine based on Article 1367 of the Indonesian Civil Code. The research methodology employs a normative juridical approach through the analysis of legislation, court decisions, and literature review. The research findings indicate that financial institutions can be held civilly liable under vicarious liability, administratively liable through sanctions from the Financial Services Authority, and under certain circumstances, criminally liable.